EKSISTENSI BANK THITHIL DALAM KEGIATAN PASAR TRADISIONAL (STUDI KASUS DI PASAR KOTA BATU) - Aldrin Ali Hamka; Tyas Danarti (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2010)
This study aims to reveal the aspects that support the existence of banks thithil oneconomic activity in the Batu Market. Using a phenomenological approach, thisstudy’s findings are 1) preferences of traders in maximizing profits as bank thithil,2) continuous interaction among traders and embedded in social networks, 3) easeof access for traditional traders who already have a network, 4) operation time ofbank thihtil more flexible than formal financial institutions, easier to be reached bytraditional traders 5) credit risk management to maintain the business.Keywords: preferences, social networks, access, flexible, credit risk management